Oral health status of newly admitted residents living in residential aged care. (5th July 2021) - Chu, K‐Y; Cockrell, D; Naganathan, V; Stanaway, F; Wright, FAC
Abstract: Background: It is important to understand whether older people are admitted into residential care with existing dental diseases or their oral health deteriorates while residing in residential care. There is, however, little research available exploring the oral health status of people newly admitted into residential care. Understanding this disease trend would lead to effective prevention and treatment strategies to be trialled and implemented prior to admission. In this cross‐sectional study, we hypothesize that older people with one or more natural teeth might have poor oral health prior to admission to residential care. Method: The study was carried out using the de‐identified oral health assessment database of an established domiciliary oral health care program in metropolitan New South Wales, Australia. Four hundred and nine participants with mean participant age of 85.56 years from 13 facilities from 2015 to 2018 fulfilled the inclusion criteria for this study. Conclusion: This study confirmed that dentate, newly admitted residents to residential care had pre‐existing dental problems and oral health concerns. Almost half of the newly admitted residents had an unsatisfactory oral cleanliness score when examined in their residential care setting.